(untitled) (The Review of Diabetic Studies, 2025)
The increasing prevalence of diabetes and cardiovascular disease in Saudi Arabia has necessitated a comprehensive evaluation of healthcare workforce contributions, particularly those of allied health technicians. This systematic review examines the roles, responsibilities, and clinical impact of pharmacy technicians, laboratory technicians, and nursing technicians in chronic disease management within the Saudi healthcare context. A systematic search of peer-reviewed literature was conducted across multiple databases, focusing on technician-specific contributions to diabetes and cardiovascular care. Results indicate that while clinical pharmacist roles have been extensively documented, pharmacy technician contributions remain underutilized and poorly defined in Saudi practice. Laboratory technicians demonstrate critical roles in point-of-care testing and quality assurance, though workforce challenges persist. Nursing technicians contribute substantially to patient education and monitoring, yet face role ambiguity and limited recognition. Findings reveal significant gaps in interprofessional collaboration frameworks and regulatory clarity regarding technician scope of practice. This review underscores the need for policy reforms, enhanced training programs, and integrated care models that optimize technician contributions to chronic disease management aligned with Saudi Vision 2030 healthcare transformation objectives.